LUO RITUALS PERTAINING TO ANCESTRAL SPIRITS’ VENERATION AND THEIR IMPLICATION ON CHRISTIAN WORSHIP - A STUDY IN THE SEVENTH-DAY ADVENTIST CHURCH, KENYA LAKE CONFERENCE - Otieno, Ogayo; Ayako, Richard; Kandago, Daniel (Journal of Philosophy, Culture and Religion, 2021)
Purpose: This study analyzed Luo rituals pertaining to ancestral spirits veneration and their implications on Christian worship practices, in the Seventh-day Adventist Church -Kenya Lake Conference. Methodology: The study adopted a descriptive research design and data was obtained through interviews, observations, and questionnaires. The findings were analyzed through MAXQDA 2020- qualitative data analysis software designed for companies which are analyzing different types of customer data as indicated by Radiker & Kuckartz (2020). Results: The results indicated that Luo rituals pertaining to ancestral spirits veneration are deeply rooted in the lives of SDA Church members and cannot be dispensed with. Moreover, Luo rituals pertaining to ancestral spirits' veneration are predominant cultural practices that seemingly engulfed every member in the community; hence affect worship practices in the Kenya Lake Conference. Unique contribution to theory and practice: The study is informed by two major theories which are: functional and essentials of religion as presented by Durkheim (1912) and Otto (1917) respectively with a burden of explaining the benefits of various Christian worship practices and cultural veneration approaches. Essential view of Otto (1917) understands religion as binding feeling of reverence characterized with awe and fascination when worshippers are in the presence of mysterium tremendous the compelling yet repelling mystery of religion